Facial asymmetry correction with surgical-orthodontic treatment: Challenges of the surgical and postsurgical phases - Sara Palmares; Rui Pereira (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2023)
Asymmetry is commonly diagnosed in orthodontic clinical practice and is more or less perceived depending on its severity. In more severe cases, orthodontic-surgical treatment is the only treatment option. Although presurgical orthodontics is fundamental, occasionally, the occlusion obtained after surgery is far from that planned, and the orthodontist must decide between surgical re-intervention or orthodontic finishing. This clinical report describes the case of an 18-year-old man, presenting a severe facial asymmetry with class III malocclusion, who underwent a surgical-orthodontic treatment. One week after orthognathic surgery, the patient was reoperated because the intercuspation was different from the one obtained at the end of surgery. However, after the second surgery, the intercuspation was still far from what was planned. Despite that, at the end of treatment, a functional and stable occlusion was obtained, associated with a significant improvement in facial harmony and function.